Anisotropic Magnetite Nanorods for Enhanced Magnetic Hyperthermia. Issue 21 (6th October 2016) - Geng, Sai; Yang, Haitao; Ren, Xiao; Liu, Yihao; He, Shuli; Zhou, Jun; Su, Na; Li, Yongfeng; Xu, Chunming; Zhang, Xiangqun; Cheng, Zhaohua
Abstract: There is an increasing need for new strategies to improve the heating efficiency or the specific absorption rate (SAR) of magnetite (Fe3 O4 ), which is the only FDA approved magnetic material. We propose a facile approach to obtain well‐dispersed highly crystalline Fe3 O4 nanorods (NRs) by the reduction of β‐FeOOH in an organic solvent and demonstrate that the SAR of Fe3 O4 NRs can be enhanced by tuning their aspect ratios. Fe3 O4 NRs with an aspect ratio of 4.5 have a much higher SAR as compared with 15 nm Fe3 O4 nanoparticles and Fe3 O4 NRs counterparts with an aspect ratio of 10. The highest SAR is greatly increased up to 1072 W g −1 for an ac field of 33 kA m −1 and a concentration of 5 mg mL −1, which is mostly attributed to hysteresis losses. These findings pave a new pathway for the design and synthesis of novel anisotropic iron oxide nanostructures with an optimal heating efficiency for advanced hyperthermia. Abstract : Well‐dispersed highly crystalline Fe3 O4 nanorods have been successfully synthesized by the reduction of FeOOH nanorods in an organic solvent. The specific absorption rate (SAR) of Fe3 O4 nanorods, with an aspect ratio of 4.5, can be greatly increased up to 1072 W/g for a concentration of 5 mg/mL and an ac field of 33 kAm ‐1 . The SAR of Fe3 O4 nanorods is much higher as compared to that of their spherical counterparts and can be enhanced by tuning their aspect ratio.